2017
DOI: 10.1002/gch2.201700048
|View full text |Cite
|
Sign up to set email alerts
|

Fate of So‐Called Biodegradable Polymers in Seawater and Freshwater

Abstract: The stability of polymers with C—C and stable C—heteroatom backbones against chemicals, hydrolysis, temperature, light, and microbes has challenged society with the problem of accumulation of plastic waste and its management worldwide. Given careless disposal of plastic waste, large amounts of plastic litter accumulate in the environment and disintegrate into microplastics. One of the questions frequently raised in the recent times is if so‐called biodegradable polymers can substitute conventional polymers for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
186
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(218 citation statements)
references
References 34 publications
7
186
0
Order By: Relevance
“…A similar trend regarding the biodegradability of PLA in soil and in artificial seawater and freshwater was seen in laboratory tests. [ 10 ] Further, it is not possible to distinguish clearly in these studies between fragmentation and biodegradation. The biodegradation should be evidenced by the conversion of organic carbon to CO 2 /methane and biomass.…”
Section: Environmental Degradability Of Classified Biodegradable Polymentioning
confidence: 99%
See 1 more Smart Citation
“…A similar trend regarding the biodegradability of PLA in soil and in artificial seawater and freshwater was seen in laboratory tests. [ 10 ] Further, it is not possible to distinguish clearly in these studies between fragmentation and biodegradation. The biodegradation should be evidenced by the conversion of organic carbon to CO 2 /methane and biomass.…”
Section: Environmental Degradability Of Classified Biodegradable Polymentioning
confidence: 99%
“…[ 14 ] There are no indications of the biodegradation of PBAT in aquatic systems over a period of at least 1 year. [ 10 ] Currently, the biodegradation under actual environmental conditions is only tested by following the visual change in the form, mass, structure, and properties of the polymer under test. The additional environmental factors, such as sunlight, wind, wind speed, and humidity, can have a significant influence on the rate and mechanism of polymer biodegradation under natural environmental conditions as photodegradation, photooxidation, and cross‐linking become significant in the natural environment.…”
Section: Environmental Degradability Of Classified Biodegradable Polymentioning
confidence: 99%
“…Furthermore, polymer degradation in marine environments is even more challenging due to the low temperatures and oligotrophic conditions that hamper microbial activity as well as the reduced encounter rate in such dilute ecosystems. Hence, although some marine microbial isolates have been reported to degrade a range of polyesters (Mabrouk and Sabry, ; Ghanem et al ., ; Sekiguchi et al ., ), such a process is not as obvious in marine environments as highlighted by studies that failed to observe degradation of some theoretically biodegradable polymers such as PHB, PES and PBS (Sekiguchi et al ., ; Bagheri et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Hence, although some marine microbial isolates have been reported to degrade a range of polyesters (Mabrouk and Sabry, 2001;Ghanem et al, 2005;Sekiguchi et al, 2010), such a process is not as obvious in marine environments as highlighted by studies that failed to observe degradation of some theoretically biodegradable polymers such as PHB, PES and PBS (Sekiguchi et al, 2010;Bagheri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that PLGA was degraded completely in both 2 environments after 270 testing days while PHB was decomposed up to 8 % after 365 testing days. [2] The tensile properties of poly(3-hydroxybutyrate-cohydroxyvalerate)/polyethylene oxide ((PHBV)/PEO) modified starch blend were decreased after 150 testing days in seawater (Puerto Rico). [3] It can be seen the development of fungi on the surface of starch and blend samples.…”
Section: Introductionmentioning
confidence: 99%